KAJIAN NORMATIF PASAL 192 UU KESEHATAN NO. 17 TAHUN 2023 TENTANG PENOLAKAN PENGOBATAN PASIEN DAN IMPLIKASI TANGGUNG JAWAB HUKUM RUMAH SAKIT - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2025)
The refusal of patient treatment by hospitals is a crucial issue that has legal and ethical consequences in health services in Indonesia. This study aims to conduct a normative review of Article 192 of Health Law No. 17 of 2023, which regulates the refusal of patient treatment and identifies the implications of legal responsibility that must be borne by hospitals. A normative juridical method was used by analysing the relevant legal provisions, doctrines, and jurisprudence to understand the meaning, scope, and legal impact of the article. The results of the study show that Article 192 provides a clear legal basis for hospitals to refuse treatment based on valid reasons and transparent procedures. However, this provision also requires hospitals to be civilly, criminally, and administratively liable if the refusal is carried out improperly. This study recommends improving legal compliance and transparency in the implementation of refusal procedures to ensure the protection of patient rights and reduce the risk of legal disputes.